2014
DOI: 10.1007/s40261-014-0197-y
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Pharmacokinetics of Lobeglitazone, a Novel Peroxisome Proliferator-Activated Receptor-γ Agonist, After a Single Oral Administration in Healthy Female Subjects

Abstract: Lobeglitazone was well-tolerated in healthy females. There was no sex difference for systemic lobeglitazone exposure at a 2 mg dose; however, female subjects showed greater systemic exposure than males after the administration of 4 mg of lobeglitazone. In spite of the pharmacokinetic difference, dose adjustment based on sex alone is not needed in clinical use because therapy should be individualized for each patient to achieve glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It was reported that fenofibrate, a PPARa agonist, may improve insulin sensitivity, probably by interactions between the drug and its receptor, as shown in an animal model of diabetes and obesity (Koh et al, 2003). Interestingly, the effective dose of LB was significantly lower than that for rosiglitazone and pioglitazone [i.e., (in effective dose) LB, 0.5 mg/d; rosiglitazone, 2-8 mg/d; pioglitazone, 15-45 mg/d] (Balfour and Plosker, 1999;Hauner, 2002;Park et al, 2014). Therefore, it is possible that the higher potency of LB may be partly mediated by the interaction of LB with PPARa.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that fenofibrate, a PPARa agonist, may improve insulin sensitivity, probably by interactions between the drug and its receptor, as shown in an animal model of diabetes and obesity (Koh et al, 2003). Interestingly, the effective dose of LB was significantly lower than that for rosiglitazone and pioglitazone [i.e., (in effective dose) LB, 0.5 mg/d; rosiglitazone, 2-8 mg/d; pioglitazone, 15-45 mg/d] (Balfour and Plosker, 1999;Hauner, 2002;Park et al, 2014). Therefore, it is possible that the higher potency of LB may be partly mediated by the interaction of LB with PPARa.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study reports the findings from healthy male subjects instead of the indicated group of T2DM patients, neither lobeglitazone nor empagliflozin showed clinically relevant differences in the pharmacokinetic characteristics by sex. 19 , 39 Nonetheless, cautious interpretation of the results and thorough monitoring are compulsory in practice.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Lobeglitazone is rapidly absorbed into the systemic circulation and is then cleared in a monoexponential manner with a negligible amount excreted in the urine. 18 , 19 SGLT-2 inhibitors and TZDs not only have different mechanisms of action in regulating blood glucose levels but also have a relatively low risk of hypoglycemia, and their synergistic effect on attenuation of the early phase of diabetic nephropathy progression further supports combination therapy as one of the preferred treatment options in the management of T2DM. 20 Therefore, a thorough evaluation of drug–drug interactions for expected concomitant drug candidates is crucial even without an index perpetrator or substrate drug.…”
Section: Introductionmentioning
confidence: 99%
“…All participants were healthy young males, which is not typical of cardiovascular patients seen in the clinical setting. There was no sex difference for systemic lobeglitazone exposure at a 2 mg dose, which is four times the approved maximum dose of 0.5 mg. 24 Because the anticoagulant response to warfarin is affected by several factors, the warfarin response must be monitored carefully even in the absence of drug interactions.…”
Section: Discussionmentioning
confidence: 99%